Interfaith Marriage in Kuningan and Jakarta: State Intervention and Human Rights - Sidiqah, Meliyani (Jurnal Ius Constituendum, 2025)
The purpose of this paper is to analyse the similarities and differences in the perspectives of various institutions in Kuningan and Jakarta and examine these views from a human rights perspective. The background of this study is the issue of legal uncertainty surrounding interfaith marriages. On one hand, it is prohibited, and the other hand it is permitted but made difficult. This research is significant as it addresses the phenomenon of interfaith marriages, which the Indonesian government has ambiguously responded to. On one hand, such marriages are permitted but made excessively difficult; on the other hand, they are prohibited but ultimately recognized. This paper employs a sociological-juridical research methodology with a comparative approach. Fieldwork was conducted in two cities, Kuningan and Jakarta, using interviews with interfaith couples and officials from local RAO, CRSO, RC, and DC. The novelty of this paper lies in its identification of human rights violations based on empirical evidence. The comparative findings from the two cities reveal that the current legal framework governing marriage in Indonesia fails to reflect certainty and justice. Furthermore, interfaith marriage remains a significant and unresolved issue in the country.